An Analysis On Student’s Difficulties In Writing Descriptive Text At Eight Grade In Upt Smpn Manarai No 18 Kepulauan Selayar - Tania, Tania; Syatriana, Eny; Daddi, Herlina (Journal of Language Testing and Assessment, 2024)
The study aimed to find out the students' difficulties in writing descriptive text and to find out the factors that cause students' difficulties in writing descriptive text at eight grade in UPT SMPN Manarai No 18 Kepulauan Selayar. In this study used descriptive qualitative method. The population of this study was eighth grade students. The research sample was VIIIB class students with a sample of 10 students. It was chosen by using purposive sampling technique. The instruments used by the researcher in this study were written texts and interviews with student.The results of this study are related to the students difficulties in writing descriptive text based on the aspect of writing and factors causing the difficulty of students in writing. This study indicated that almost all students have difficulty in aspects writing. In the aspect of content, students get an average score of 2.9 it was can classified as very poor. In the aspect of organization, students get an average score of 2.2 it was can classified as very poor. In the aspect of grammar, students get an average score of 1.3 it was can classified as very poor. In the aspect of vocabulary, students get an average value of 1.7 it was can categorized as very poor. Some of these difficulties are caused by several factors, namely, students did not like English lessons, lack of mastery of students vocabulary, lack of students motivation to learn, unattractive learning media, and lack of attention from parents in terms of student education.